(untitled) (Homoeopathy for All, 2022)
Osteoarthritis (OA) is by far the most common form of arthritis and is a major cause of pain and disability in older people.1 OA is a disorder characterized by progressive joint failure in which all structures of the joint have undergone pathologic change. The pathologic sign of OA is hyaline articular cartilage loss accompanied by increasing thickness and sclerosis of the sub chondral bone plate, outgrowth of osteophytes at the joint margin, stretching of the articular capsule, and weakness of the muscles bridging the joint. There are numerous pathways that lead to OA, but the initial step is often joint injury in the setting of a failure of protective mechanisms.2